Digital Banking in Nepal: Embracing the Potential During the COVID-19 Pandemic - Joshi, Bhuwan Raj; Joshi, Pusp Raj (Journal of Durgalaxmi, 2023)
The digital banking system was introduced with the innovation and advancement of information and communication technology but because of the hesitancy of customers and the lack of initiation from the banks, it did not keep pace in Nepal. In this context, the epidemic of COVID-19 seemed to have a noticeable impact on accelerating digital banking, even though it has caused great damage in other areas of social life. This study seeks to provide a comparative analysis of before and during COVID-19 on customer access and effectiveness of digital banking services, and changes in customer behavior. The research uses annual reports of NRB, newspapers, and article reviews as secondary data and semi-structured interviews with banking customers and bank employees as sources of primary data. This research examines how the COVID-19 pandemic has affected digital banking in Nepal, and it may also serve as a model for future studies in the area. This study found that in the post-pandemic scenario customer access to digital banking services has significantly increased and it consequently led to an increase in customer confidence and it is helpful to reduce the cost of digital transactions. This study will also be helpful to make digital banking more effective.